Membangun City Branding Lokalitas dalam Tumbler Starbucks: Suatu Pendekatan Budaya - Gunawan Wiradharma (PERSPEKTIF, 2022)
This research aims to provide a comprehensive overview of how Tumbler Starbucks City Series Indonesia builds city branding on displayed cities. The method used in this study is qualitative with several supporting techniques such as library study techniques, listen, and record. The results of this study showed that the Tumbler Starbucks City Series can be said to "successfully" display a form of local wisdom such as highlighted elements of dance culture, traditions, and landmarks. Nonetheless, the process in building city branding has not been able to be a strong parameter in an effort to increase tourists. There are several problems that can be felt in the application of city branding in the cover tumbler Starbucks City Series. First, the branding implications contained on this tumbler cover have some contradictions between marketing goals and communication goals. Second, the city image built on a Starbucks City Series tumbler is limited to traditional landmarks and dance. Third, the relatively expensive price of tumblers is also a major drawback to the city branding process in Starbucks tumblers.